Undoing - Atkinson, Peter. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Music.; Advisor: John McDonald.; Committee: Alessandra Campana, and Michael McLaughlin.; Keyword: Musical composition.